Potential effects of male socialization on therapeutic skills development - Rocha Junior, José Edberto Gadelha; Marques, Natália Santos; Oshiro, Claudia Kami Bastos (Perspectivas em Análise do Comportamento, 2023)
The literature on therapeutic skills considers that technical, theoretical and especially social therapeutic skills are essential to the development of therapy. However, in sexist and patriarchal societies, while women are exposed to contingencies of reinforcement of behaviors that relate to caring and emotional expression, men are taught to behave aggressively, to contain their emotions and to participate less in caregiving practices. In view of these conditions, this work aims to revisit the literature on therapeutic skills in the light of debates on masculinity, discussing potential incompatibilities between the highlighted skills and characteristic features of hegemonic masculinity in Western culture. Among the main results, it is pointed out that most of the skills highlighted by the literature correspond to social repertoires incompatible with the parameters of male socialization. In this sense, it is emphasized that the process of male socialization potentially competes with the learning of essential repertoires for the progress of therapy. Such discussions point to the importance of considering gender issues in the training, performance and supervision of therapists. It also highlights the contribution of the literature on gender to the production of knowledge in behavioral therapies.